2014
DOI: 10.1097/mph.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Iron-deficiency Anemia and Autoimmune Atrophic Gastritis in Pediatric Age Group

Abstract: AAG must be recognized as a pathology affecting pediatric patients. Gastric autoimmune lesion is a chronic process with potential evolution to malignancy. Management guidelines in childhood are not available. Their elaboration is important considering an important risk factor in these age group: a long life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
(40 reference statements)
1
14
0
3
Order By: Relevance
“…The long-term outcome of AIG in children has not been investigated yet. Our findings, in line with those of other authors, have shown no improvement in gastric atrophy, metaplasia, or ECL cell hyperplasia over time, consistently with known progression of AIG in adult patients ( 3 , 4 , 8 , 10 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The long-term outcome of AIG in children has not been investigated yet. Our findings, in line with those of other authors, have shown no improvement in gastric atrophy, metaplasia, or ECL cell hyperplasia over time, consistently with known progression of AIG in adult patients ( 3 , 4 , 8 , 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…The same observation was made by other authors who followed-up pediatric patients with H. pylori infection and AIG ( 9 , 10 ). However, as H. pylori eradication is a simple procedure most of the times, regular search and treatment in case of positivity are recommended ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that refractory or unexplained IDA should increase clinicians’ suspicion of AMAG not only in adults but also in pediatric population. 59 – 61 PA is the most common cause of cobalamin deficiency. 62 Although the underlying mechanisms of how cobalamin deficiency causes megaloblastosis have not been fully elucidated, it is believed that it is due to cobalamin’s essential role in DNA synthesis.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Interestingly, 3 of these patients had normal VitB12 levels 18 . Autoimmune gastritis has been reported in children with IDA, 17‐19 type 1 diabetes mellitus, 20 Sjögren syndrome, 21 autoimmune thyroid disease, 22,23 and autoimmune hepatitis 24 . We identified Behcet's disease in a child with AIG which represents a new coincidence.…”
Section: Discussionmentioning
confidence: 81%
“…Autoimmune atrophic gastritis is a very rare entity in children, and there are only a few reports in the literature 16‐21 . It was first reported in 1972 in a child with hemolytic anemia, thrombocytopenia, and autoantibody 16 .…”
Section: Discussionmentioning
confidence: 99%